2009
DOI: 10.1590/s0100-69912009000400010
|View full text |Cite
|
Sign up to set email alerts
|

Perfil epidemiológico e fatores prognósticos no tratamento cirúrgico do adenocarcinoma de próstata clinicamente localizado

Abstract: OBJETIVO: Avaliar a evolução e os fatores prognósticos da prostatectomia radical. MÉTODOS: Um total de 500 pacientes foi submetido à prostatectomia radical, entre 2000 e 2006. Estádio clínico, PSA pré-operatório e escore de Gleason foram avaliados em conjunto com o estádio patológico e margens cirúrgicas. O seguimento foi feito pela monitorização do PSA e correlação com diversos critérios. RESULTADOS: Dos 500 pacientes com doença clinicamente localizada tiveram seguimento médio de 36,7 ± 18,8 meses. O tempo op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
0
0
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 38 publications
2
0
0
4
Order By: Relevance
“…The mean age, race, and preoperative PSA level of our patients were in agreement with those reported in previous studies. 1 4 14 The TNM tumor stage was in agreement with that of a recent study by Nassif et al (65% of patients were pT2c); however, the average tumor stage of patients in this study was different from that of recent international reports. 14 For instance, a study on 369 patients by Freedland et al in the United States reported that the predominant TNM tumor stage was pT2a (34% of patients).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The mean age, race, and preoperative PSA level of our patients were in agreement with those reported in previous studies. 1 4 14 The TNM tumor stage was in agreement with that of a recent study by Nassif et al (65% of patients were pT2c); however, the average tumor stage of patients in this study was different from that of recent international reports. 14 For instance, a study on 369 patients by Freedland et al in the United States reported that the predominant TNM tumor stage was pT2a (34% of patients).…”
Section: Discussionsupporting
confidence: 90%
“… 1 4 14 The TNM tumor stage was in agreement with that of a recent study by Nassif et al (65% of patients were pT2c); however, the average tumor stage of patients in this study was different from that of recent international reports. 14 For instance, a study on 369 patients by Freedland et al in the United States reported that the predominant TNM tumor stage was pT2a (34% of patients). 9 Another study performed in United States by Makarov et al reported the predominant stage of 5730 patients as pT1c (77% of patients).…”
Section: Discussionsupporting
confidence: 90%
“…Um estudo realizado por Nassif (2009) [26] demonstrou que a maior incidência de desenvolvimento da doença é na sexta década de vida, oscilando na faixa etária de 50 -79 anos, apontando a idade como um dos fatores determinantes para o desenvolvimento do câncer de próstata. Dessa forma, nossos dados corroboram com os achados de outros autores em que a faixa etária mais acometida pela neoplasia compreende idades entre 60 -79 anos.…”
Section: Discussionunclassified
“…Considerando as características cirúrgicas, o escore (12,17) . Outros dois, apenas para o Gleason, sendo o estádio mais frequente o T1c (60% e 77%) (18)(19) .…”
Section: Muitos Tumores Clinicamente Classificadosunclassified